Quality of worklife of pharmacists in the Philippines - Danganan, Jillian B.​; Guinto, Kim Michelle P.​; Velasquez, Zadkiel F.​; Gloria, Mac Ardy J.​ (​​​​​​​​​​Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2017)
Quality of worklife (QWL) is a multidimensional construct that relates with an individual?s personal and work lives. It is of importance for health professionals with its influences on the quality of care, treatment outcomes, health expenses, and public safety. To date, there are no studies examining the QWL of pharmacists in the Philippines. This study employed a descriptive, correlational design to assess QWL in terms of the following dimensions: stress in the work environment, control in the work environment, job satisfaction, professional commitment, work-home conflict, and organizational commitment. Stratified random sampling, based on fields of practice, of members from the 2015 Philippine Pharmacists Association (PPhA) Database was conducted. These members were then invited to participate in the study through electronic mails and a text message. Of the 2,476 contacted, 292 (11.79%) responses were usable. Results revealed several significant differences in the mean dimension scores based on the demographic and work-related variables. Correlations between the dimensions were also found. Stress was negatively correlated with professional commitment, and positively with work-home conflict. Control was negatively correlated with work-home conflict, and positively with satisfaction, professional and organizational commitment. Satisfaction was positively correlated with professional and organizational commitment. Professional commitment was negatively correlated with work-home conflict, and positively with organizational commitment. Lastly, work-home conflict was negatively correlated with organizational commitment. Generally, the respondent-pharmacists reported a not too stressful work environment, having moderate control, positively in job satisfaction, professional commitment, and organizational commitment, and negatively in work-home conflict. However, since the sample size was not achieved, there is reduced generalizability of the key findings and a possibility that the significant differences were found by chance. Nonetheless, the findings of this study serve as baseline information for use in future researches, to further understand and enhance the quality of worklife of pharmacists in the country. For the improvement of the study, strategies may be implemented to increase the response rate, such as having printed survey questionnaires as an alternative to online data collection or implementation of both. Moreover, the tool may be enhanced by accurately identifying which variables and dimensions are of relevance in assessing QWL of pharmacists in the Philippines through focused-group discussions or key informant interviews.
Available to the general public.
​​​​​​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2017. ​
Keywords: Quality of work life; Pharmacists